The Influence of the News Message Content of the Bandar Lampung City Government in Lidik.id Media on Information Satisfaction of the People of Way Halim District - Yugo Dwi Prasetio; Tina Kartika (International journal of technology and education research, 2023)
According to the Association of Indonesian Internet Service Providers (APJII), internet users in Indonesia are increasing and are quite high. In 2018, the results of a survey conducted by APJII found 171.1 million people or 73.7% increasing to 196.71 million people from internet use in Indonesia in a population of 266.91 million Indonesian population in 2019. (APJII, 2019). This research is to find out what are the contents of news messages from the City Government of Bandar Lampung and to find out how much the effectiveness of the use of dik.id media is in fulfilling the information needs of the people of Way Halim District. The Uses and Gratification model views individuals as suprarational and active beings, receiving criticism, however, the uses and gratification model changes attention so that it shifts from the process of sending messages to receiving messages. The core of the uses and gratifications theory is the idea that media users depend on media information in meeting their needs and achieving goals, where the model assumes three ways of interacting, the media, media users and society, which influence the media to interact. The concept of user satisfaction for media lik.id is divided into two, namely (1) the Gratifications Souhgt motive and (2) the satisfaction obtained. Satisfaction with the site based on the gap between gratifications sought and gratifications obtained. The smaller the discrepancy, the more satisfying. Meanwhile, the greater the discrepancy, the more unsatisfactory. Gratifications Sought is the satisfaction that users want in using the media, or the user chooses or does not choose the media because it is based on the motive of fulfilling the need. Research on motives for using the internet is used as a motive for media consumption. Satisfaction obtained as a result of using the media is the need for information, the need for personal identity, the need for integrity and interaction, and the need for entertainment